Early movement restriction leads to enduring disorders in muscle and locomotion - Delcour, Maxime (Brain Pathol, 2018)
Motor control and body representation in the central nervous system (CNS) as well as musculoskeletal architecture and physiology are shaped during development by sensorimotor experience and feedback, but the emergence of locomotor disorders during maturation and their persistence over time remain a matter of debate in the absence of brain damage. By using transient immobilization of the hind limbs, we investigated the enduring impact of postnatal sensorimotor restriction (SMR) on gait and posture on treadmill, age‐related changes in locomotion, musculoskeletal histopathology and Hoffmann reflex in adult rats without brain damage. SMR degrades most gait parameters and induces overextended knees and ankles, leading to digitigrade locomotion that resembles equinus. Based on variations in gait parameters, SMR appears to alter age‐dependent plasticity of treadmill locomotion. SMR also leads to small but significantly decreased tibial bone length, chondromalacia, degenerative changes in the knee joint, gastrocnemius myofiber atrophy and muscle hyperreflexia, suggestive of spasticity. We showed that reduced and atypical patterns of motor outputs, and somatosensory inputs and feedback to the immature CNS, even in the absence of perinatal brain damage, play a pivotal role in the emergence of movement disorders and musculoskeletal pathologies, and in their persistence over time. Understanding how atypical sensorimotor development likely contributes to these degradations may guide effective rehabilitation treatments in children with either acquired (ie, with brain damage) or developmental (ie, without brain injury) motor disabilities.